PARADIGMA BARU ASESMEN PEMBELAJARAN: INTEGRASI PENILAIAN OTENTIK DAN DEEP LEARNING DALAM MEMBANGUN KOMPETENSI ABAD KE-21 - deni sutisna; nursaptini Nursaptini; Hairil wadi (Jurnal Pendidikan Sosial Keberagaman, 2026)
21st-century education is driving a paradigm shift in learning and assessment. Traditional methods, limited to content mastery, are transforming into the development of critical thinking, collaborative, and communicative competencies, as well as problem-solving skills. In this context, the concepts of authentic assessment and Deep Learning are approaches that require attention in creating more advanced and modern educational reforms. This article aims to analyze the conceptual and empirical relationship between authentic assessment and Deep Learning to support 21st-century learning. It uses a narrative literature review approach, employing thematic analysis techniques to provide clear boundaries for the analysis process and generate a synthesis. The reviewed literature represents research results or government policies published between 2021 and 2026. For journal articles, the criteria set must be derived from nationally accredited journals with a minimum of Sinta 4 and reputable international articles. The analysis shows that authentic assessment has a catalytic function in realizing Deep Learning through authentic and realistic tasks that focus on assessment processes such as performance, attitude, and portfolio assessments. The Deep Learning approach requires an assessment system that can measure higher-order thinking processes. A literature synthesis shows that the integration of authentic assessment and immersive learning contributes to the development of 21st-century competencies and the enhancement of meaningful learning. This article offers a conceptual model of the relationship between authentic assessment and immersive learning as a foundation for learning development in the era of educational transformation. Keywords: Learning Assessment; authentic Assessment, Deep Learning, 21st Century Skills